Analisis Kinerja Keuangan Pt Bank BJB Tahun 2019-2023 - Gio Argenis; Hilman Abdul Halim (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
(Bank BJB) during the 2019-2023 period using profitability ratios, including Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Gross Profit Margin (GPM). The research method employed is descriptive with a quantitative approach, based on secondary data obtained from Bank BJB's annual financial statements. The analysis results indicate that, despite fluctuations, Bank BJB has generally managed to maintain its financial performance within reasonable limits. The ROA and ROE ratios reflect efficiency in asset and equity management, while the NPM and GPM ratios demonstrate the bank's ability to generate net profit from operational income. Although there was a decline in net profit in 2023, Bank BJB has maintained performance stability through the implementation of digitalization strategies and effective cost management. This study provides practical implications for Bank BJB's management to enhance operational efficiency and profitability. Furthermore, the findings can be utilized by stakeholders to assess the bank's financial stability and devise sustainable development strategies.